2020
DOI: 10.1080/10826084.2020.1717538
|View full text |Cite
|
Sign up to set email alerts
|

Trends in Binge and Heavy Drinking among Adults in the United States, 2011–2017

Abstract: Background: Alcohol misuse is one of the leading causes of preventable death in the United States each year. Objectives: In the present study, we examine trends in binge and heavy drinking. We used data from the 2011–2017 Behavioral Risk Factor Surveillance System. For trend analyses, we used logistic regression for heavy drinking and binge drinking variables. Joinpoint model analysis was conducted to identify where significant changes in trend occurred. Results: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
11
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 42 publications
2
11
1
Order By: Relevance
“…In bivariate analyses, we examined distributions of patient demographic and health characteristics by alcohol consumption levels. Consistent with prior studies (Azagba et al, 2020; Grant et al, 2017; McKee et al, 2007), higher proportions of men, younger patients (18 to 34 vs. ≥65 years), and patients who smoke exceeded only daily limits and both daily and weekly limits relative to the overall sample. We also found differences in risk profiles among patients with unhealthy alcohol use.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…In bivariate analyses, we examined distributions of patient demographic and health characteristics by alcohol consumption levels. Consistent with prior studies (Azagba et al, 2020; Grant et al, 2017; McKee et al, 2007), higher proportions of men, younger patients (18 to 34 vs. ≥65 years), and patients who smoke exceeded only daily limits and both daily and weekly limits relative to the overall sample. We also found differences in risk profiles among patients with unhealthy alcohol use.…”
Section: Discussionsupporting
confidence: 86%
“…In bivariate analyses, we examined distributions of patient demographic and health characteristics by alcohol consumption levels. Consistent with prior studies (Azagba et al, 2020; Psychiatric disorders were identified using ICD-9-CM and ICD-10-CM codes in the electronic health record in the year prior to (and including) the date of the alcohol screening visit. b…”
Section: Discussionmentioning
confidence: 99%
“…The KPNC Adult Alcohol Registry can evaluate the full course of alcohol problems, longitudinally and comprehensively, including early identification, initiation and engagement in treatment (including psychiatry, addiction medicine, and pharmacotherapy), and long-term outcomes (eg, drinking, physical and mental well-being), which are critical to understanding recovery. The prevalence of unhealthy alcohol use was 13%, which falls within the range reported by prior studies of the general US population (6%-28%) [ 16 , 17 ]. However, the prevalence of AUD diagnoses in our population (3%) was lower than the 2012-2013 prevalence of Diagnostic and Statistical Manual of Mental Disorders-5 (DSM-5) AUD (13.9% [ 32 ]) and DSM-IV AUD (12.6%, [ 18 ]) estimated from surveys of the general US population, which might be because diagnoses in health systems depend on clinician assessment and diagnosis during utilization of health care services.…”
Section: Discussionsupporting
confidence: 79%
“…Alcohol can also impact the course of disease progression, management, and treatment outcomes for a range of conditions, including diabetes [ 12 ], depression [ 13 , 14 ], and anxiety [ 15 ]. While the prevalence of excessive alcohol use in the general US population ranges from 6% to 28% (depending on the definition and whether individuals with an AUD diagnosis are included) [ 16 , 17 ], there is evidence that it is increasing [ 17 , 18 ]. Therefore, alcohol problems are a significant public health concern that would benefit from being the primary focus of a disease registry.…”
Section: Introductionmentioning
confidence: 99%
“…Each year, 3.3 million deaths worldwide are attributable to alcohol consumption, with an expected increasing trend over the next decade [ 72 ]. A recent study reported an increase in binge drinking behavior among the general population [ 73 ]. In particular, binge drinking is commonly diffused among younger adults.…”
Section: Discussionmentioning
confidence: 99%